Kepastian Hukum Payment Guarantee Memitigasi Resiko Kontrak Bank dan Developer - Hendrik Fasco Siregar; Siti Nurwulan; Frieda Fania (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2021)
The biggest risk of cooperation agreements will be experienced by Banking business actors, the specific nature of banks as credit lenders in the end requires prudence in contracting to avoid losses, payment guarantee instruments or buying back assets can be considered in the agreement system or cooperation contract. to mitigate the risk of loss to the Bank because with the buyback guarantee there is at least a special bond between the Developer and the Bank so that it will provide legal certainty. The instrument payment guarantee or asset repurchase in the deed of the cooperation agreement between the Bank and the Developer is useful for guaranteeing payment and for mitigating the risk of the Bank in the event of a bad debtor in payment, this is because the Bank cannot execute guarantees that have not been bound by the Deed of Mortgage.